A computational model for the ionic self-assembly of nanoparticles under the influence of external electric fields. (November 2019) - Baker, E.; Withers, M. O.; Aldrich, E.; Shaffrey, I.; Pusztay, J.; Mazilu, D. A.; Mazilu, I.
Abstract: We present a class of cooperative stochastic models for adsorption and evaporation of monomers on two- and three-dimensional lattices subjected to perpendicular external electric fields. These models are motivated by the fabrication of optical coatings using layer-by-layer self-assembly. We report computational and analytical results for the time-dependent particle density and discuss a particular experimental implementation of an ionic self-assembled monolayer under the influence of external electric fields.